2011
DOI: 10.1016/j.alcohol.2011.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol metabolism activates cell cycle checkpoint kinase, Chk2

Abstract: Chronic ethanol abuse results in hepatocyte injury and impairs hepatocyte replication. We have previously shown that ethanol metabolism results in cell cycle arrest at the G2/M transition, which is partially mediated by inhibitory phosphorylation of the cyclin-dependent kinase, Cdc2. To further delineate the mechanisms by which ethanol metabolism mediates this G2/M arrest, we investigated the involvement of upstream regulators of Cdc2 activity. Cdc2 is activated by the phosphatase Cdc25C. The activity of Cdc25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Benzo(a)pyrene diol epoxide, present in tobacco smoke, is suggested to increase ATM expression in premalignant and malignant esophageal tissues . Ethanol metabolism increased the active forms of ATM in hepatocyte . Low‐dose arecoline (15.5 μg/mL) treatment enhances the genotoxicity of benzo(a)pyrene by suppressing DNA repair in HEp‐2 cells .…”
Section: Discussionmentioning
confidence: 99%
“…Benzo(a)pyrene diol epoxide, present in tobacco smoke, is suggested to increase ATM expression in premalignant and malignant esophageal tissues . Ethanol metabolism increased the active forms of ATM in hepatocyte . Low‐dose arecoline (15.5 μg/mL) treatment enhances the genotoxicity of benzo(a)pyrene by suppressing DNA repair in HEp‐2 cells .…”
Section: Discussionmentioning
confidence: 99%
“…The G2/M checkpoint, which functions as cells mitosis stunner, is considered to be a conspicuous target for anticancer drugs. There are many essential proteins involved in G2/M phase transformation, including cyclin B1, cdc2, and p27 13 . In addition, Apoptosis and autophagy are known as a major cellular molecular mechanism to regulate cancer progression and maintain the homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Detection of these adducts by the cell activates the checkpoint kinases and arrests the cell cycle progression. In previous studies, we demonstrated that ethanol metabolism by VA-13 cells activates ataxia-telangiectasia mutated (ATM), which in turn activates the checkpoint kinase Chk2 [ 15 ]. Chk2 can phosphorylate Cdc25c the phosphatase that activates Cdc2.…”
Section: Discussionmentioning
confidence: 99%
“…This impairment in cellular replication is, at least partially, the result of a G2/M cell cycle arrest. Furthermore, this G2/M cell cycle arrest is mediated, at least in part, by the activation of cell cycle check point kinases and the accumulation of the cyclin dependent kinase, Cdc2, in the inactive, phosphorylated form [ 1 , 15 ].…”
Section: Introductionmentioning
confidence: 99%